Differences between transthoracic echocardiography and transthoracic echocardiography on hemodynamics and inflammatory stress response in patients with severe aortic stenosis - Deng, Fanxin; Chen, Aidong; Chen, Bin; Yang, Bo; Shi, Xiaoming; Xu, Zhipeng (Journal of Medical Biochemistry, 2025)
Background: Transcatheter aortic valve replacement (TAVR) is currently the main approach for treating severe aortic stenosis (AS), and preoperative echocardiography is a necessary measure. In this research, we analyzed the application value of transthoracic echocardiography (TTE) and transesophageal echocardiography (TEE) in TAVR, aiming to provide more reliable reference opinions for future clinical implementation of TAVR for patients with severe AS. Methods: 204 patients with severe AS who were treated with TAVR in our hospital from January 2022 to February 2024 were selected as the research subjects. Among them, 109 patients received TTE (TTE group), and another 95 patients received TEE (TEE group). Differences in the evaluation effects of preoperative echocardiography and multislice helical computed tomography (MSCT) in all patients were compared, and changes in echocardiographic parameters before and after surgery were observed. In addition, the differences in postoperative hemodynamics, cardiac function, stress response, inflammatory factors and pain mediators between the observation and TTE groups were compared.Results: No differences were identified in the evaluation of the aortic root between echocardiography and MSCT (P>0.05). After surgery, parameters such as LVESD and IVST decreased, while LVEF and AVA increased (P
Keywords: Transesophageal echocardiography; Aortic stenosis; Transthoracic echocardiography; Inflammatory factors; Stress response